105 Value of Atlas-Based Data and Intraoperative Testing in Deep Brain Stimulation. (April 2023) - Paulo, Danika Lea; Narasimhan, Saramati; Gonzalez, Hernan F. J.; Allen, Jackson; Li, Rui; Rodriguez, William; Konrad, Peter; Neimat, Joseph; Shah, Hamid M.; Bick, Sarah K. B.; Dawant, Benoit M.; Englot, Dario J.
Abstract : INTRODUCTION: Deep brain stimulation (DBS) is commonly performed awake to collect intraoperative microelectrode recordings (MER) and macrostimulation to optimize efficacy and minimize side effects (Bour et al, 2010). With supplementary information from an atlas-based database (CranialVault), efficacy heat maps guide initial targeting, intraoperative final electrode position (FEP) selection and post-operative programming (D'Haese et al, 2012). A better understanding of how this data is integrated to inform all stages of DBS can assist in reducing OR time, optimizing electrode position, expediting programming, and enhancing patient outcomes. METHODS: 451 individual patients who underwent DBS for Parkinson's Disease, Essential Tremor or Dystonia, treated with 822 individual leads, at Vanderbilt University Medical Center between 2011-2021 were included. Intraoperative testing data including MER firing rate, macrostimulation efficacy and coordinates of FEP were retrieved from the CranialVault database. Average coordinates of planned target, midpoint and bottom of FEP, active contact and centroid of heat maps per target in patient space were calculated and visualized. Medical charts were reviewed for 1-year post-operative outcomes. RESULTS: The distribution of FEPs per target include 55.2% of leads placed in center track. Average coordinates in patient space of planned target, centroid of heatmap, midpoint and bottom of FEP and active contact were recorded. MER data demonstrates how multiunit activity changes at different depths relative to target, per target. Patients who achieve 4th quartile efficacy intraoperatively are more likely to achieve maximal benefit at 1-year post-op (p = 0.003, chi-squared). CONCLUSIONS: Atlas-based data and intraoperative testing is valuable, often leads to changes in FEP and can predict post-operative outcomes.